Retrospective Study: Atopic Dermatitis in Childhood - Kristina Sihaloho; Diah Mira Indramaya (Faculty of Medicine, Universitas Airlangga, 2015)
Background: Atopic dermatitis is a chronically and relapsing inflammatory skin disease affecting individuals with atopic history or their families. Atopic dermatitis affects all ageswith percentage 15-30% in children and 1-2% in adults. Chronic pruritus, skin infection, sleep disorder, and growth disorder are signs and symptomps commonly found in childhood atopic dermatitis. Evaluation of the profile and management of DA were needed to improve the management of atopic dermatitis. Purpose:To evaluate the profile of childhood atopic dermatitis. Methods: A retrospective study of all new cases of childhood atopic dermatitis who visited the Pediatric Division, Dermatology and Venereology Outpatient Clinic, Dr. Soetomo General Hospital, Surabaya from January 2007 to Desember 2011. Results: Numbers of chilhood atopic dermatitis increased from 2007 to 2011. Itchy was the main complaint of DA, but redness patches (32,3%) and xerosis cutis (9,1%) were also found. Atopic history in patients and or their families were found in 842 patients (74,3%). Treatment was antihistamin in 879 patients (77,5%). Conclusions: Chilhood atopic dermatitis are still increasing by years. Determining and avoiding trigger factors are education for DA's patients and their families in preventing it recurrency.Key words: atopic dermatitis, childhood, retrospective study.